Effects of Ciliate Infection on the Activities of Two Antioxidant Enzymes (SOD and CAT) in Captive Coral (Goniopora columna) and Evaluation of Drug Therapy - Chiu-Min Cheng (MDPI AG, 2021)
Ciliate infection is a serious parasitic disease of coral. Infected coral rots and dies in a short time. In addition to killing corals by infecting them in the oceans, ciliate infection also poses a threat to corals farmed on a large scale. In this study, two antioxidant enzymes (SOD and CAT) were used to judge the stress response in Goniopora columna after infection, and KCl and H2O2 were used to evaluate the therapeutic effect. The results showed that SOD and CAT increased during the early stage of infection but decreased with the extension of infection time. In terms of drug therapy, it was found that the treatment of ciliate infection with 1.5% of KCl had no significant effect on SOD and CAT of G. columna. The morphological changes of zooxanthellae, chlorophyll a, and coral were not significant. H2O2 leads to a stress response and polyp contraction. In conclusion, 1.5% of KCl can be used in the selection of drugs to treat ciliate infection.